2006
DOI: 10.1128/aac.00418-06
|View full text |Cite
|
Sign up to set email alerts
|

Effective Prevention of Microbial Biofilm Formation on Medical Devices by Low-Energy Surface Acoustic Waves

Abstract: Low-energy surface acoustic waves generated from electrically activated piezo elements are shown to effectively prevent microbial biofilm formation on indwelling medical devices. The development of biofilms by four different bacteria and Candida species is prevented when such elastic waves with amplitudes in the nanometer range are applied. Acoustic-wave-activated Foley catheters have all their surfaces vibrating with longitudinal and transversal dispersion vectors homogeneously surrounding the catheter surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 21 publications
1
95
0
3
Order By: Relevance
“…Potentially, this is difficult to consistently achieve and would constitute a significant risk to any in vivo applications. Hazan et al demonstrated what might be considered the most advanced step towards achieving clinical implementation using acoustic energy to date in a rabbit model where catheters utilizing piezo-electric actuators remained sterile for up to 9 days whilst all controls developed UTIs [85]. Further studies must be carried out to develop a matrix of which acoustic treatment parameters are effective at targeting a broad range of bacterial species.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
See 3 more Smart Citations
“…Potentially, this is difficult to consistently achieve and would constitute a significant risk to any in vivo applications. Hazan et al demonstrated what might be considered the most advanced step towards achieving clinical implementation using acoustic energy to date in a rabbit model where catheters utilizing piezo-electric actuators remained sterile for up to 9 days whilst all controls developed UTIs [85]. Further studies must be carried out to develop a matrix of which acoustic treatment parameters are effective at targeting a broad range of bacterial species.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
“…Novel efforts have been made to combat device-related bacterial infections by using acoustic energy at specific frequencies to either prevent biofilm formation on surfaces or to mechanically compromise the structures of existing biofilms [85,86]. Acoustic energy holds a number of key advantages over other methods as it can prove an effective means of bypassing the conditioning-film and hence preventing any surface adhesion occurring in the first place since the mechanical disruptions render any firm surface attachment much more difficult.…”
Section: Biofilm Prevention and Control Using Acoustic Energymentioning
confidence: 99%
See 2 more Smart Citations
“…The antigenicity of the alginate lyase must be considered before the enzyme can be developed for clinical use. Recently, it was reported that ultrasonic vibrations block bacterial biofilms from forming on medical devices, 70) although physical processes must be constructed to maintain continuous vibration to prevent biofilm formation.…”
Section: Alginate Biofilms and Bacterial Infectionmentioning
confidence: 99%